REDESAIN PASAR MODERN SANTA MENJADI PASAR BERKELANJUTAN YANG INKLUSIF DI PETOGOGAN, JAKARTA SELATAN - Michelle Britney Chen; Tony Winata (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The digital transformation experience happened to Santa Modern Market, it is a block Q neighborhood market in Petogogan, Kebayoran Baru, South Jakarta has degraded since 2016, marked by the closure of several kiosks by business actors due to the decreasing number of visitors. The cause of degradation is defined in several aspects, namely; 1. Social Aspect (FOMO, digital transformation, social talk), 2. Memory aspect (Loss of inclusiveness for the elderly), 3. Physical aspect (entrance placement and circulation to chaotic sites), 4. Systematic Aspect (Indication of gentrification). The purpose of re-designing Santa Modern Market is to maintain the identity of Santa Modern Market as a local market in the Q block area, conducting new activity programs along with its program spaces to support the development of digitalization and market sustainability, as well as facilities that can attract the attention of newcomers outside the local market and maintain inclusiveness for all beings so the results of the design execution can restore the glory of Santa Modern Market as an inclusively sustainable Mixed Commercial Space by using the Pragmatic Perspective Method to overcome the degradation phenomenon of Pasar Santa. Keywords:  Digital Transformation; Inclusive; Mixed Commercial Space; Santa Modern Market; Sustainable Abstrak Pengalaman transformasi digital dialami oleh Pasar Modern Santa yang merupakan Pasar lingkungan blok Q di Petogogan, Kebayoran Baru, Jakarta Selatan. Mengalami degradasi sejak tahun 2016, ditandai penutupan sejumlah kios oleh pelaku usaha karena pengunjung yang terus berkurang. Penyebab degradasi diuraikan menjadi beberapa aspek, yaitu ; 1. Aspek Sosial (FOMO, transformasi digital, latah sosial), 2. Aspek Memori (Kehilangan inklusifitas bagi kaum lansia), 3. Aspek Fisik (Penataan entrance masuk dan sirkulasi menuju tapak semrawut), 4. Aspek Sistematik (Indikasi Gentrifikasi). Tujuan mendesain kembali Pasar Modern Santa adalah mempertahankan identitas Pasar Modern Santa sebagai pasar lingkungan blok Q, penambahan fungsi program ruang aktivitas yang mendukung perkembangan digitalisasi dan keberlanjutan pasar, serta fasilitas yang mampu menarik perhatian pendatang di luar lingkungan pasar dan inklusif terhadap seluruh kalangan. Sehingga dapat mengembalikan Kembali kejayaan Pasar Modern Santa sebagai Mixed Commercial Space berkelanjutan yang inklusif. Menggunakan Metode Perspektif Pragmatik dalam mengatasi fenomena degradasi Pasar Santa.